2014
DOI: 10.1007/s11999-013-3139-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Cementless Stems More Durable Than Cemented Stems in Two-stage Revisions of Infected Total Knee Arthroplasties?

Abstract: Background The routine use of stems in revision TKA improves survival rates by enhancing the stability of the prosthesis. The ideal method of stem fixation (cemented or uncemented) in two-stage reimplantation remains controversial. Questions/purposes The purpose of this study was to answer the following questions: (1) Are rerevision rates for aseptic loosening comparable between cemented stems and uncemented stems in two-stage reimplantation? (2) Is the reinfection rate comparable between antibiotic-impregnate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 39 publications
7
37
1
Order By: Relevance
“…While they found similar survivorship, reinfection, and clinical outcomes at 52 months postoperatively, cemented stems were significantly more likely to have radiographic loosening (32 vs. 17%, p ¼ 0.0006). 42 The only meta-analysis addressing this question was performed by Wang et al When examining 17 observational studies, they found no superiority of either stem, with no significant difference in reoperation, aseptic loosening, and infection. 43 After a thorough evaluation of the best evidence in the literature, it is clear that no consensus can be made about cementing versus hybrid fixation of stems in rTKA.…”
Section: Outcomes and Conclusionmentioning
confidence: 99%
“…While they found similar survivorship, reinfection, and clinical outcomes at 52 months postoperatively, cemented stems were significantly more likely to have radiographic loosening (32 vs. 17%, p ¼ 0.0006). 42 The only meta-analysis addressing this question was performed by Wang et al When examining 17 observational studies, they found no superiority of either stem, with no significant difference in reoperation, aseptic loosening, and infection. 43 After a thorough evaluation of the best evidence in the literature, it is clear that no consensus can be made about cementing versus hybrid fixation of stems in rTKA.…”
Section: Outcomes and Conclusionmentioning
confidence: 99%
“…The results of this study of only the revision TKA femoral component are difficult to compare with other series of femoral components with C and UC stem fixation because of the variety of stem lengths used, severity of femoral metaphyseal defi-ciency, inclusion of both femoral and tibial stems in most studies, numbers of patients, and length of follow-up 1,2,[16][17][18][19][20][21] (►Table 3). Fehring et al reported no loosening or aseptic revisions in 54 C stem revisions and 17% aseptic revision or loosening in 47 UC stem at 5 years follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…There have been studies advocating fully C femoral components with stems of variable length and UC fixation of the femoral stem extension of variable lengths, with cement fixation of the metaphyseal surface only (so-called hybrid fixation). [16][17][18][19][20][21] There are specific advantages and possible disadvantages with both techniques, thus a consensus has not been reached and there are no guidelines for specific use. The advantages of cemented fixation of the femoral stem include added fixation of the component in fresh metaphyseal and diaphyseal bone, flexibility in distorted bone geometries, and delivery of Note: These numbers do not add up to 50 and 34 knees respectively and % does not add up to 100% because some knees had no augments and some had more than one.…”
Section: Discussionmentioning
confidence: 99%
“…Stems are used to decrease strain at the bone-cement interface (distal femur or proximal tibia) by transferring the load to a larger area in order to provide additional mechanical stability for component fixation [71]. Stems can be cemented or cementless (press-fit) [72,73]. Table 2 shows a comparison of cemented and cementless stem techniques in rTKA with a minimum 24-month follow-up.…”
Section: Stemsmentioning
confidence: 99%